Novel neuroprotective tetramethylpyrazine analog T-006 promotes neurogenesis and neurological restoration in a rat model of stroke. Issue 9 (12th June 2019) - Wu, Liangmiao; Cao, Jie; Li, Ning; Chen, Haiyun; Liu, Wei; Zhang, Gaoxiao; Liu, Yu; Wang, Yuqiang; Sun, Yewei; Zhang, Zaijun
Abstract : Neuronal death is among the deleterious pathological changes that occur after cerebral ischemia and can lead to transient or permanent neurological deficits. The tetramethylpyrazine analog T-006 has been shown to be a multifunctional neuroprotective agent; however, its neuroprotective effect and mechanism of action have not been studied in ischemic stroke model rats. This study investigated the neuroprotective effects of T-006 in rat stroke model using a battery of behavioral and molecular biological tests. Results indicated that T-006 treatment significantly improved neurological function and behavior. Double immunofluorescence staining showed that T-006 visibly improved the number of NeuN + /BrdU +, Nestin + /BrdU +, and DCX + /BrdU + cells and induced neuronal regeneration. Western blot analyses indicated that T-006 upregulated neurogenesis-related protein expression of postsynaptic density protein 95, brain-derived neurotrophic factor, synaptophysin, and myelin basic protein. Collectively, these data suggest that T-006 stimulated neurogenesis in rats with middle cerebral artery occlusion and restored neurological functions.